2019
DOI: 10.26650/ekoist.2018.14.29.0012
|View full text |Cite
|
Sign up to set email alerts
|

Does Women Well-being Matter for Demand and Development of Children?

Abstract: Women well-being has number of socioeconomic and developmental implications. Early child development is directly linked with well-being of mothers and educated women demand lower children. However, the existing literature hardly focused this area, therefore, the current study has investigated the impact of women wellbeing on fertility and early child development. For this purpose, this study constructed women well-being index to measure the well-being of the women by using four dimensions, economic well-being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…According to the Theory of Moral Sentiments, a personal sense of well-being is related to their belief in the way others treat them (Kilburn et al, 2019). Simultaneously, Qasim et al (2018) depicted that social security, a sense of respect, and feelings of self-worth among women arise due to society and governments recognizing their role in contributing positively to society. Moreover, the Normative Theory of Human Rights believes that protection of social and economic women rights increases their motivation to contribute positively to society (Sultana et al, 2017); hence, fulfilling socioeconomic women rights ensures their well-being through the promotion of feelings of security, safety, and justice.…”
Section: Women's Socio-economic Rights and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Theory of Moral Sentiments, a personal sense of well-being is related to their belief in the way others treat them (Kilburn et al, 2019). Simultaneously, Qasim et al (2018) depicted that social security, a sense of respect, and feelings of self-worth among women arise due to society and governments recognizing their role in contributing positively to society. Moreover, the Normative Theory of Human Rights believes that protection of social and economic women rights increases their motivation to contribute positively to society (Sultana et al, 2017); hence, fulfilling socioeconomic women rights ensures their well-being through the promotion of feelings of security, safety, and justice.…”
Section: Women's Socio-economic Rights and Well-beingmentioning
confidence: 99%
“…Women's well-being has been related to freedom of choice, right to education and career, childbirth, and property inheritance in general, among others (Qasim et al, 2018). Well-being has been related to the feelings of gratitude, forgiveness, and altruism, associating it as a positive emotional outcome due to satisfaction with one's surroundings and interpersonal relationships (Kilburn et al, 2019).…”
Section: Mediation Of the Socio-economic Rights Of Women Between Positive Religious Coping And Well-beingmentioning
confidence: 99%
“…Because females make up over half of Bangladesh's population, it is safe to say that their economic situation is steadily growing more favorable. In terms of a country's long-term economic prosperity and success, empowering women is about more than just maintaining the fundamental rights granted by the constitution and international accords [6] . According to Hossain [7] , women in Bangladesh, a developing nation with a Muslim majority in the "typical patriarchal belt", have made great strides regarding access to education, healthcare, and the workforce in the recent two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the inconsistent findings of recent research on the current field, compelling reasons exist to prioritize this issue for both instrumental and intrinsic motivations. At the same time, there is evidence that women's empowerment increases when they have access to financial resources [6,[15][16][17][18][19] . However, some studies have discovered an inconsistent relationship between financial inclusion and women empowerment [20,21] ; while Neaime and Gaysset [22] found that financial inclusion has no discernible effect on poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Physical health, mental health, and well-being trajectories are established in the youth and adolescence stages. Qasim et al [ 21 ] found that women’s well-being is significantly associated with early child development. In a previous study, Walker et al [ 22 ] showed lower well-being; low satisfaction is significantly associated with low birth weight, stunting, decreasing children’s survival, and many other complications.…”
Section: Introductionmentioning
confidence: 99%